Inside CKD: a microsimulation modelling study projects the clinical and economic burden of chronic kidney disease in Hungary - Szabó, Lilla; Halmai, Luca Adél; Ladányi, Erzsébet; Garcia Sanchez, Juan Jose; Barone, Salvatore; Cabrera, Claudia; Retat, Lise; Webber, Laura; Wittmann, István; Laczy, Boglárka (Frontiers in Nephrology, 2024)
ObjectivesThe Inside CKD programme implemented a microsimulation modelling approach to project the clinical and economic burden of chronic kidney disease (CKD) between 2024 and 2027 in Hungary.MethodsUsing the peer-reviewed Inside CKD microsimulation, a virtual Hungarian population was generated that was derived from national records, local demographic data and published epidemiological data. These inputs defined the likelihood of a change in health state for each individual as they progressed through the model in annual increments. Individual CKD status, including disease progression, cardiorenal complications and associated costs, was tracked annually to generate the population-level projections of the clinical and economic burden of CKD.ResultsBy 2027, people with CKD were projected to constitute 13.3% of the Hungarian national population. The prevalence of heart failure, myocardial infarction and stroke in people with CKD were projected to remain consistently high, reaching 323 447, 69 188 and 120 118 by 2027, respectively. Kidney replacement therapy cases were predicted to remain high at 20 515 in 2024 and 22 325 in 2027, with associated costs increasing from 71.4 billion HUF in 2024 to 79.6 billion HUF in 2027. Total annual healthcare costs associated with treating CKD were projected to constitute 5.4% of the overall national healthcare budget in 2027.ConclusionsInside CKD demonstrates that the future burden of CKD in Hungary will be substantial unless current management strategies change. The high prevalence of undiagnosed CKD and associated cardiorenal complications highlight the urgent need for policy interventions focused on early diagnosis and timely intervention to mitigate the future burden of CKD.